Axial Scanning Metal‐Induced Energy Transfer Microscopy for Extended Range Nanometer‐Sectioning Cell Imaging. Issue 7 (4th December 2021) - Hwang, Wonsang; Kim, Dongeun; Kim, Dugyoung
Abstract: Nanometer‐sectioning optical microscopy has become an indispensable tool in membrane‐related biomedical studies. Finally, many nanometer‐sectioning imaging schemes, such as variable‐angle total internal reflection fluorescence microscopy, metal‐induced energy transfer (MIET) imaging, and supercritical‐angle fluorescence microscopy have been introduced. However, these methods can measure a single layer of molecules, and the measurement ranges are below 100 nm, which is not large enough to cover the thickness of lamellipodium. This paper proposes an optical imaging scheme that can identify the axial locations of two layers of molecules with an extended measurement range and a nanometer‐scale precision by using MIET, axial focal plane scanning, and biexponential analysis in fluorescence lifetime imaging microscopy. The feasibility of the proposed method is demonstrated by measuring an artificial sample of a known structure and the lamellipodium of a human aortic endothelial cell whose thickness ranges from 100 to 450 nm with 18.3 nm precision. Abstract : Axial scanning metal‐induced energy transfer (AS‐MIET) microscopy can be combined with a conventional confocal FLIM system by adding an axial scanning apparatus and using a simple data analysis algorithm. It is anticipated that AS‐MIET microscopy can make practical 3D imaging of cell organelles possible and become a vital tool for various membrane‐related studies and structural cell biology.